Offshore BPO at large captive operations in India - Penter, Kevan; Pervan, Graham; Wreford, John (Emerald Group Publishing Limited, 2009)
Purpose: The purpose of this paper is to contribute towards development of a managementframework for offshore business process outsourcing (BPO). Design/methodology/approach: This paper utilises longitudinal case studies to identify successfactors in managing offshore BPO via the captive model (i.e. wholly-owned subsidiary). Findings: Success in offshore BPO is based on a combination of cost savings, technical servicequality and strategic issues, is specific to business context and will change over time. Choice ofengagement model (e.g. captive operation or arms-length contracting) is an important success factor. Advantages of captive centers arise from higher levels of relationship quality, trust and collaborationeffectiveness. Research limitations/implications: This paper focuses on two global companies in two industrysectors (airlines and telecommunications), and both have adopted one particular BPO model (i.e.captive operation). Originality/value: The paper contributes to scarce literature on offshore captive BPO operations,the most common but also least researched engagement model. The findings have practicalimplications for managers designing offshore BPO strategy.